Pharmacological Properties and Molecular Mechanisms of Thymol: Prospects for Its Therapeutic Potential and Pharmaceutical Development - Nagoor Meeran, Mohamed Fizur; Javed, Hayate; Al Taee, Hasan; Azimullah, Sheikh; Ojha, Shreesh K. (Frontiers in Pharmacology, 2017)
Thymol, chemically known as 2-isopropyl-5-methylphenol is a colorless crystalline monoterpene phenol. It is one of the most important dietary constituents in thyme species. For centuries, it has been used in traditional medicine and has been shown to possess various pharmacological properties including antioxidant, free radical scavenging, anti-inflammatory, analgesic, antispasmodic, antibacterial, antifungal, antiseptic and antitumor activities. The present article presents a detailed review of the scientific literature which reveals the pharmacological properties of thymol and its multiple therapeutic actions against various cardiovascular, neurological, rheumatological, gastrointestinal, metabolic and malignant diseases at both biochemical and molecular levels. The noteworthy effects of thymol are largely attributed to its anti-inflammatory (via inhibiting recruitment of cytokines and chemokines), antioxidant (via scavenging of free radicals, enhancing the endogenous enzymatic and non-enzymatic antioxidants and chelation of metal ions), antihyperlipidemic (via increasing the levels of high density lipoprotein cholesterol and decreasing the levels of low density lipoprotein cholesterol and low density lipoprotein cholesterol in the circulation and membrane stabilization) (via maintaining ionic homeostasis) effects. This review presents an overview of the current in vitro and in vivo data supporting thymol’s therapeutic activity and the challenges concerning its use for prevention and its therapeutic value as a dietary supplement or as a pharmacological agent or as an adjuvant along with current therapeutic agents for the treatment of various diseases. It is one of the potential candidates of natural origin that has shown promising therapeutic potential, pharmacological properties and molecular mechanisms as well as pharmacokinetic properties for the pharmaceutical development of thymol.